Aerothermodynamics modelling of complex shapes in the DEBRISK atmospheric reentry tool: Methodology and validation. (June 2020) - Annaloro, Julien; Galera, Stéphane; Thiebaut, Cédric; Spel, Martin; Van Hauwaert, Pierre; Grossir, Guillaume; Paris, Sébastien; Chazot, Olivier; Omaly, Pierre
Abstract: To predict the debris survivability during an atmospheric re-entry and assess the prospective risk on ground, CNES develops an engineering tool named DEBRISK, based on an object-oriented approach. This approach is currently limited to primitive shapes and is therefore difficult to apply to more complex shapes. The objective of this work is to present a new methodology, based on the MISTRAL software, to introduce more complex shapes within DEBRISK with the goal to deal accurately with the atmospheric re-entry of more realistic objects. Moreover, this new methodology is validated by setting up an experimental campaign performed in the Von Karman Institute Longshot wind tunnel. Highlights: Prediction of debris survivability during an atmospheric re-entry and risk on ground. Implementation of complex shapes within DEBRISK, the CNES′ object-oriented code. Efficiency atmospheric re-entry simulations. CFD numerical database construction. Validation of the methodology by experimental tests.